2022
DOI: 10.20885/jkek.vol1.iss2.art11
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh uang elektronik terhadap pertumbuhan ekonomi di Indonesia tahun 2011-2020

Abstract: Purpose – This paper aims to analyze the effect of electronic money payment instruments and macroeconomic variables - inflation, exchange rates, foreign direct investment, and the labor force - economic growth. Methods – This study uses the Vector Error Correction Model (VECM) method to determine the relationship amongst variables in the long and short run. The data is a quarterly time series for the period 2011:1-2020:4. Findings – The research finds that transactions using electronic money have a positive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The results of this study are in line with the results of research found by Placencia (2022) which states that electricity infrastructure has a positive and significant effect on GRDP in provinces in the special autonomous region of Indonesia. Similar results were also found in a study conducted by Amalia (2019) whose research results stated that electricity infrastructure had a positive and significant effect on GDP in provinces in Indonesia.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study are in line with the results of research found by Placencia (2022) which states that electricity infrastructure has a positive and significant effect on GRDP in provinces in the special autonomous region of Indonesia. Similar results were also found in a study conducted by Amalia (2019) whose research results stated that electricity infrastructure had a positive and significant effect on GDP in provinces in Indonesia.…”
Section: Discussionsupporting
confidence: 88%
“…Pertemuan dengan komunitas perempuan bertujuan untuk memotivasi dan mendorong keterlibatan perempuan secara aktif di Kecamatan Cipongkor dan Rongga yang diikutsertakan dalam program pemberdayaan perempuan di bidang UMKM. Selain itu, keterlibatan komunitas perempuan juga dapat mendukung program pemberdayaan yang inklusif dan membuka potensi kolaborasi dan pertukaran sumber daya yang dapat memperkuat program pemberdayaan (Amalia, 2023;Hariyono, 2020;Mahmudi, 2023). Oleh karena itu, Tim PPM mengadakan pertemuan dengan Fatayat Nahdlatul Ulama Pimpinan Cabang Kabupaten Bandung Barat (Fatayat NU PC KBB) dan Sapa Institute.…”
Section: Pelaksanaan Fgd Dengan Komunitas Perempuanunclassified
“…Each type of infrastructure has a specific function that is influenced by various factors in its context. As a key driver of economic growth, infrastructure acts as a locomotive for development, allocating resources from the public and private sectors at the national and local levels [1]. The infrastructure of a region is closely related to the character of its people, so that some infrastructure characteristics are very closely related to the daily lives of its people [2].…”
Section: Introductionmentioning
confidence: 99%